Übelkeit und Erbrechen in der Onkologie: Ursachen, Diagnose, Therapie = Nausea and vomiting in oncology : Causes, diagnosis, and treatment - Hübner, Jutta; Jordan, Karin (Der Onkologe, 2019)
Nausea and vomiting are common side effects of radio- and chemotherapy that affect the quality of life and represent a health risk. Emesis is controlled by the general pattern generator in the medulla oblongata. It is mediated by neurotransmitters such as serotonin, substance P, and dopamine. The risk for emesis is mainly determined by cytostatics, the type of radiotherapy, and to an extent by individual factors. There are three forms of emesis: acute, delayed, and anticipatory. Emesis prevention is preferred over therapy. Acute emesis is prevented with 5‑hydroxytryptamine (HT)3 receptor antagonists. In the case of a high risk of emesis, they are combined with neurokinin (NK)1 receptor antagonists and corticosteroids. Delayed emesis prophylaxis consists mainly of the last two. Anticipatory emesis is initiated by psychological processes; therefore, the reduction of fear and negative emotions is key.
Online publiziert: 11. Dezember 2018
Gesehen am 22.07.2019